The Interaction between Visual and Proprioception Information for Dynamic Postural Control in Healthy Individuals - yasin hoseini; Nader Farahpour (Biyumikānīk-i varzishī)
Objectives: Poor dynamic balance may expose an individual to the risk of falling. The role of proprioception systems have been well addressed in the literature; however, majority of previous studies have been conducted in static conditions. The main objective of this study was to evaluate the dynamic postural control of healthy individuals during perturbation on their base of support in eyes opened and closed conditions. Methods: Forteen healthy men participated in this study. To measure dynamic postural ability, the subjects stood on a four weel cart. Then using the force of a load equal to 10% of the subject’s body mass, the cart was moved forward. A motion analysis system with Falcon cameras (240Hz) was used to quantify the kinematic variables of the head, trunk, hip, knee and ankle joints during the test. Tests were repeated while the eyes were closed. For statistical analysis repeated measure analysis of variance was used with p<0.05. Results: The range of motion in head, trunk, hip, knee and ankle joints were 23.17º±1.8, 21.56º±3.51, 22.15 º ±2.16, 32.72º±3.29 and 19.93 º±2.18 respectively. The results showed that closing eyes would result in the reduction of the range of motion in various joints. Conclusion: the posture is controled mostly by the motion in the knee joint rather than the hip or ankle joints. It is recommended to enhance the knee extensors to prevent falling in people with high risk of postural instability.